Intranasal Osteosarcoma in a Dog—A Case Report - de Toledo, Gabriela Noronha [UNESP]; Reina Moreira, Pamela Rodrigues [UNESP]; Rolemberg, Daniele Santos [UNESP]; Facin, Andréia Coutinho [UNESP]; Hough Monteiro, Julio Edward [UNESP]; Menezes, Mareliza Possa de [UNESP]; Bastos Andrade Moutinho da Conceição, Maria Eduarda [UNESP]; Ruiz Sueiro, Felipe Augusto; Oliveira Vasconcelos, Rosemeri de [UNESP]; Castro Moraes, Paola de [UNESP]; Costa, Mirela Tinucci [UNESP]; de Nardi, Andrigo Barboza [UNESP] (Elsevier, 2018)
Osteosarcoma is the most commonly reported bone tumor in dogs, typically affecting the axial and appendicular skeleton. Involvement of the paranasal sinuses and the nasal cavity is extremely rare. This report describes a 6-year-old, female, cross-breed dog presented with signs of 90 days duration and diagnosed with a mass located in the right nasal cavity. Radiography, rhinoscopy, and computed tomography findings suggested the presence of an intranasal tumor. Osteosarcoma in the nasal cavity was diagnosed based on histopathological examination and clinical and imaging findings. Survival time was 12 months from diagnosis.
Keywords: bone tumor; dog; neoplasia; veterinary pathology (source: MeSH)